Customer Satisfaction Based on Service Quality and Price - Rahayu, Feni Sri; Andari, Titiek Tjahja; Yulianingsih (MultiTech Publisher, 2024)
Industrial machine repair services is one of the service industries where new company actors have emerged and innovated as a result of the growth of the service sector. One strategy to outperform the competition is to prioritize customer satisfaction. A few important factors that affect customer satisfaction are price and the quality of the services rendered. The purpose of this study is to ascertain how pricing and service quality at PT. Karya Utama Wijaya Sakti relate to each other in terms of customer satisfaction. The sample size is one hundred clients, and multiple linear regression analysis is the method employed. The study's findings show that, albeit slightly concurrently, both the pricing and the quality of services at PT. Karya Utama Wijaya Sakti have a positive and significant impact on customer satisfaction.